Scoping the impact of COVID-19 on the nexus of statelessness and health in Council of Europe member states - Marie Claire Van Hout; Charlotte Bigland; Nina Murray (Elsevier, 2021)
Background: Stateless communities in Europe include ethnic Russians in the Baltic States, recent migrants, refugees, Roma, and other members of minority groups. Increases in COVID-19 infection have been observed in many European countries, including reported outbreaks in groups that include people and communities affected by statelessness, who often live in congested and sub-standard unhygienic conditions, work in informal sectors which hampers their adherence to public health measures (self-isolation/physical distancing/hand sanitation), or who are detained in immigration detention centres. The impact of COVID-19 on stateless people in Europe (estimated to be at least 600,000) is currently under researched, and there is an imperative to understand their experiences and situation, in order to generate evidence based measures, responses and actions to protect those most at risk. Method: In order to better understand their unique position during the COVID-19 pandemic, we conducted a scoping review to explore and assess the nexus between statelessness and health during COVID-19 in Europe. Literature was found representing ten Council of Europe countries (Bulgaria, Denmark, Greece, Italy, Romania, Russia, Slovakia, Ireland, Ukraine and the United Kingdom), with 15 publications representing multiple countries. Four publications specifically focused on stateless people. The remainder focused on populations which include people disproportionately affected by statelessness both in the migratory context and those in situ (minority groups including Roma and ethnic Russians, and refugees and migrants). Results: Three themes emerged from the analysis (Environmental determinants of health; access to healthcare services; and racism and vilification), with higher level abstraction centring on the nexus between existing adverse environmental determinants of health, compounded barriers to access healthcare during COVID-19; and the concerning rise in hate crime and scapegoating of minority populations during the COVID-19 emergency. Whilst the right to healthcare is a fundamental human right, with universal application and with access to healthcare services ensured to every human being without regards to race, religion or other criteria, including nationality status, this appears not to be the case for populations affected by statelessness during the COVID-19 health and state emergency. The right to a nationality (and realisation of the right to health and access to healthcare/public services) in the current pandemic times is crucial in a targeted effective and culturally sensitive public health response. Conclusion: The hidden nature of statelessness, coupled with the marginalisation of stateless people, exacerbates the structural underpinning and interplay between statelessness, human rights, health rights and right to nationality during the COVID-19 pandemic. The review further highlights the need to protect stateless people. We further cannot underestimate the need for sensitive legal, health and social response measures to tackle disease transmission in vulnerable groups, continued statelessness of people in Europe, and hate crime, xenophobia and discrimination of those perceived to be at risk of contagion.